Modelagem estratigráfica do intervalo cenomaniano-turoniano, formações Açu e Jandaíra, na borda sudoeste da Bacia Potiguar - Garcia, Gustavo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Stratigraphic modeling of depositional systems, based on the physical equations for creation of accommodation space and sedimentation rate, can simulate with reasonable approximation the stratigraphic architecture of depositional sequences through time. Applying this methodology, this study aimed at the development of a numerical model of sedimentation filling between the Middle Cenomanian and the Upper Turonian in the southwestern edge of the onshore Potiguar Basin in northeastern Brazil. This stratigraphic level is characterized by a gradual transition from the siliciclastic succession of the Açu Formation to the carbonate system of the Jandaíra Formation. To achieve the proposed objectives, five key stratigraphic surfaces were identified, three of which were sequence limits (LS1, LS2 and LS3) and two maximum flooding surfaces (SIM1 and SIM2), constituting two 3rd order depositional sequences. Sequence 1 (bottom) and Sequence 2 (top) are represented by transgressive and highstand depositional systems tracts. The simulations using the Dionisos® software had an excellent calibration with the lithological and Gamma Rays profiles in 9 wells evenly distributed in the study area. The simulated results of the transgressive systems tracts of Sequence 1, deposited between 95 (LS1) and 93.6 Ma (SIM1), consist of siliciclastics with a fining upward profile. In the highstand depositional systems tracts of Sequence 1 (between 93.6 - SIM1- and 92.8 Ma - LS2), the simulated lithofacies featured a coarsening upward profile during the siliciclastic sedimentation. Carbonate sedimentation favored by a conspicuous reduction in siliciclastic input (around 60%) started at 93 Ma, due to a climatic change or supposedly an interaction between tectonics and climate. The modeled lithofacies of the transgressive systems tracts of Sequence 2, deposited between 92.8 (LS2) and 92 Ma (SIM2), are made up of a mixed sedimentation, with a predominance of carbonates...

A modelagem estratigráfica de sistemas deposicionais, baseada nas equações físicas de criação de espaço de acomodação e taxa de sedimentação, pode reproduzir no tempo, com razoável aproximação, as arquiteturas estratigráficas das sequências deposicionais. Empregando-se esta metodologia, esta pesquisa teve como principal meta a elaboração de um modelo numérico de preenchimento sedimentar entre o Mesocenomaniano e o Neoturoniano da borda sudoeste da Bacia Potiguar emersa. Este intervalo estratigráfico é caracterizado pela passagem gradual da sucessão siliciclástica da Formação Açu para o sistema carbonático da Formação Jandaíra. Para alcançar o objetivo proposto, foram identificadas cinco superfícies estratigráficas-chave, sendo três limites de sequências (LS1, LS2 e LS3) e duas superfícies de inundações máximas (SIM1 e SIM2), constituindo duas sequências deposicionais de 3a ordem: Sequência 1 (inferior) e Sequência 2 (superior), representadas por tratos de sistemas deposicionais transgressivo e de mar alto. As simulações, utilizando-se o software Dionisos®, foram calibradas com excelente correspondência aos perfis litológicos e Raios Gama de 9 poços bem distribuídos na área estudada. Os resultados das litofácies simuladas do trato de sistemas transgressivos da Sequência 1, depositadas entre 95 (LS1) e 93,6 Ma (SIM1), são constituídas por siliciclásticos, com perfil de granodecrescência ascendente. No trato de sistemas de mar alto da Sequência 1, acomodados entre 93,6 (SIM1) e 92,8 Ma (LS2), as litofácies simuladas se caracterizam por um perfil de granocrescência ascendente durante a sedimentação siliciclástica. A partir de 93 Ma, inicia-se a sedimentação carbonática favorecida por uma conspícua redução do aporte siliciclástico (da ordem de 60%) relacionada a uma variação climática ou supostamente a uma interação entre tectônica e clima. Nos tratos de sistemas transgressivos...
Keywords: Geology, Stratigraphic; Geologia estratigráfica; Geologia estrutural; Modelagem geologica; Carbonatos; Bacias sedimentares; Potiguar, Bacia (RN e CE)